2006
DOI: 10.1590/s0066-782x2006001800027
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil para o tratamento da hipertensão arterial pulmonar idiopática

Abstract: Phosphodiesterase inhibitors like sildenafil have already been shown to improve functional capacity and hemodynamics in the treatment of pulmonary arterial hypertension. Few studies address the effects of new phosphodiesterase inhibitors as tadalafil. We report a case of a patient with idiopathic pulmonary arterial hypertension in functional class IV (New York Heart Association) with significant response to treatment with tadalafil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…29 The PDE5 inhibitors were originally developed for treatment of erectile dysfunction and today these molecules can be used in other diseases, such as benign prostate hyperplasia and pulmonary hypertension. 13,30,31 The effect of PDE5 inhibitors on testicular torsion is conflicting in the literature. Beheshtian et al demonstrated beneficial effects of sildenafil administration before detorsion in an I/R rat model.…”
mentioning
confidence: 99%
“…29 The PDE5 inhibitors were originally developed for treatment of erectile dysfunction and today these molecules can be used in other diseases, such as benign prostate hyperplasia and pulmonary hypertension. 13,30,31 The effect of PDE5 inhibitors on testicular torsion is conflicting in the literature. Beheshtian et al demonstrated beneficial effects of sildenafil administration before detorsion in an I/R rat model.…”
mentioning
confidence: 99%
“…Novos inibidores seletivos da 5-fosfodiesterase, vardenafil e tadalafil, com o mesmo mecanismo de ação, porém com propriedades fármaco-cinéticas próprias, foram igualmente lançados para o tratamento da disfunção erétil, mas poucos estudos existem sobre a sua utilização na HP (Carvalho et al, 2006 (2004), devido à sua capacidade de bloquear a ação vasoconstritora da endotelina, resulta na melhora na função hemodinâmica cardiopulmonar e ao retardo na progressão da doença. Esta substância tem sido e estudado na medicina e também demonstrou eficácia em animais no estudo experimental realizado por Clozel e colaboradores (2005).…”
Section: Tratamentounclassified
“…Several case reports provide anecdotal evidence of acute and chronic reductions in pulmonary vascular resistance, improved functional capacity and increased exercise capacity after administration of tadalafil 10–20 mg every 36–48 hours (Palmieri et al 2004; Affuso et al 2006; de Carvalho et al 2006; Deibert et al 2007; Kim et al 2007). There are two additional small case series of patients with PAH treated with tadalafil.…”
Section: Outcomes Achieved With Tadalafil In Clinical Developmentmentioning
confidence: 99%